Lipopolysaccharide-Induced Systemic Inflammation in the Neonatal Period Increases Microglial Density and Oxidative Stress in the Cerebellum of Adult Rats - Pires, Jaime Moreira; Foresti, Maira Licia; Silva, Clivandir Severino; Rêgo, Débora Bandeira; Calió, Michele Longoni; Mosini, Amanda Cristina; Nakamura, Thabatta Karollynne Estevam; Leslie, Ana Teresa F.; Mello, Luiz Eugênio (Frontiers in Cellular Neuroscience, 2020)
Inflammatory processes occurring in the perinatal period may affect different brain regions resulting in neurologic sequelae. Injection of lipopolysaccharide (LPS) at different neurodevelopmental stages produces long term consequences in several brain structures, but there is scarce evidence regarding alterations in the cerebellum. The aim of this study was to evaluate the long term consequences for the cerebellum of a systemic inflammatory process induced by neonatal LPS injection. For this, neonatal rats were randomly assigned to three different groups: Naive, Sham and LPS. Saline (sham group) or LPS solution (1 mg/kg) were intraperitoneally injected on alternate postnatal days (PN) PN1, PN3, PN5 and PN7. Spontaneous activity was evaluated with the open field test in adulthood. The cerebellum was evaluated for different parameters: microglia and Purkinje cell densities, oxidative stress levels and TNF-α mRNA expression. Our results show that administration of LPS did not result in altered spontaneous activity in adult animals. Our data also indicate increased oxidative stress in the cerebellum, as evidenced by an increase in superoxide fluorescence by dihydroethidium (DHE) indicator. Stereological analyses indicated increased microglia density in the cerebellum that was not accompanied by Purkinje cell loss or altered tumor necrosis factor alpha (TNF-α) expression in adult animals. Interestingly, Purkinje cells ectopically positioned in the granular and molecular layers of the cerebellum were observed in animals of the LPS group. Our data suggest that neonatal LPS exposure causes persistent cellular and molecular changes to the cerebellum, indicating the susceptibility of this region to systemic inflammatory insults in infancy. Further investigation of the consequences of these changes and the development of strategies to avoid those should be subject of future studies.